UPAYA PEMBERDAYAAN DAN PENINGKATAN KEPEDULIAN MASYARAKAT TERHADAP MASJID SEBAGAI SARANA KEAGAMAAN - Kukuh Santoso (VICRATINA, 2019)
Optimizing the function of mosques in the lives of Muslims is not determined by the grandeur of the mosque building alone. Many large mosques are found, but there are no congregations and minimal activities. However, it should be grateful if in the last decade there have been quite a lot of people who have been active in various activities, such as routine recitation, religious and family consultations, economic empowerment of the people and others. For that what is needed should be synchronizing the empowerment of the potential of the mosque with the empowerment of social and educational potential for the benefit of the people. One of the problems in Sonowangi Village is lack. community concern for mosque-based empowerment optimization, the function of mosques as centers of civilization change, in particularin terms of education and religious activities. I think Sensitivity social towards the younger generation in realizing that Islamic generation golden and superior and religious.